Short communication: Length-weight relationship and condition factor of the nine fish species of bycatch from Northeast Brazilian Coast - Hugo Leandro Santos; Fabricio S. Santana; Fernanda D.S. Gonçalves; Matheus S. Deda; Amanda S. Carvalho; Peterson E.G. Paixão; Higo A. Abe (Syiah Kuala University, 2022)
The length-weight relationship (LWR) and relative condition factor (Kn) are essential biometric tools in fishery studies. They provide information about the fish's growth, condition, and suitability in its habitat. LWR values were estimated for nine fish (Chloroscombrus chrysurus, Larimus breviceps, Nebris microps, Odontognathus mucronatus, Paralonchurus brasiliensis, Pellona harroweri, Ointmentsys corvinaeformis, Selene setapinnis, Stellifer rastrifer) captured as bycatch in shrimp trawling from commercial trawls, were collected monthly, between March and November 2019. The coefficient b ranged from 2.7547 to 3.4100 and the Fulton and relative condition factor ranged from 0.39 to 1.38 and 1.00 to 1.02, respectively. The current study would provide baseline data about LWR and the relative condition factor for these species captured in northeast Brazilian coast. These data are valuable for establishing a monitoring and management system for this fish species